Assessing the causes and consequences of gut mycobiome variation in a wild population of the Seychelles warbler - Sarah F. Worsley; Charli S. Davies; Maria-Elena Mannarelli; Jan Komdeur; Hannah L. Dugdale; David S. Richardson (Microbiome, 2022)
Abstract Background Considerable research has focussed on the importance of bacterial communities within the vertebrate gut microbiome (GM). However, studies investigating the significance of other microbial kingdoms, such as fungi, are notably lacking, despite their potential to influence host processes. Here, we characterise the fungal GM of individuals living in a natural population of Seychelles warblers (Acrocephalus sechellensis). We evaluate the extent to which fungal GM structure is shaped by environment and host factors, including genome-wide heterozygosity and variation at key immune genes (major histocompatibility complex (MHC) and Toll-like receptor (TLR)). Importantly, we also explore the relationship between fungal GM differences and subsequent host survival. To our knowledge, this is the first time that the genetic drivers and fitness consequences of fungal GM variation have been characterised for a wild vertebrate population. Results Environmental factors, including season and territory quality, explain the largest proportion of variance in the fungal GM. In contrast, neither host age, sex, genome-wide heterozygosity, nor TLR3 genotype was associated with fungal GM differences in Seychelles warblers. However, the presence of four MHC-I alleles and one MHC-II allele was associated with changes in fungal GM alpha diversity. Changes in fungal richness ranged from between 1 and 10 sequencing variants lost or gained; in some cases, this accounted for 20% of the fungal variants carried by an individual. In addition to this, overall MHC-I allelic diversity was associated with small, but potentially important, changes in fungal GM composition. This is evidenced by the fact that fungal GM composition differed between individuals that survived or died within 7 months of being sampled. Conclusions Our results suggest that environmental factors play a primary role in shaping the fungal GM, but that components of the host immune system—specifically the MHC—may also contribute to the variation in fungal communities across individuals within wild populations. Furthermore, variation in the fungal GM can be associated with differential survival in the wild. Further work is needed to establish the causality of such relationships and, thus, the extent to which components of the GM may impact host evolution. Video Abstract